Photo 2006 - Pedersen, B. Martin, 1936-; Kresen, Natalie; Miller, Carla (Graphis, 2005)
GraphisPhotographyAnnual2006 A stylistic four de force, this is the definitive yearbook of photographic art with an emphasis placed on commercial assignments. The 300+ photos, in most instances one per page, represent the year's best international commercial photography. Full indices of photographers and repressentatives, as well as camera/film information make this book an essential resource for art directors and art buyers.
Obsahuje rejstřík a adresář.
Keywords: fotografie; ročenky